2017
DOI: 10.1080/10640266.2017.1279908
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of a gratitude-based and cognitive restructuring intervention for body dissatisfaction and dysfunctional eating behavior in college women

Abstract: Researchers have investigated the efficacy of a gratitude intervention for decreasing body dissatisfaction (BD) in an internet treatment-seeking sample and demonstrated it worked equally well to decrease BD as cognitive restructuring. We extend this research by testing the efficacy of a gratitude intervention on BD, along with common sequelae of BD: dysfunctional eating, negative mood, and depressive symptoms. Females were randomly assigned to Gratitude, Cognitive Restructuring, or Control conditions. Pre- to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(37 citation statements)
references
References 24 publications
0
36
0
1
Order By: Relevance
“…The EPHPP assessment (Thomas et al, 2004; see Table 3) revealed that the methodological quality of studies was mixed. Six studies were classified as weak, implying a high risk of bias (Albertson et al, 2015;Duarte et al, 2017;Jankowski et al, 2017;Mellor et al, 2017;Pinto-Gouveia et al, 2017;Pinto et al, 2003), six as moderate (Ahmadi et al, 2017;Annesi, 2005;Rodgers et al, 2018;Toole & Craighead, 2016;Wolfe & Patterson, 2017) and three (by the same author and using the same intervention) as strong, implying a low risk of bias (Alleva, Diedrichs, Halliwell, Martijn, et al, 2018;Alleva, Diedrichs, Halliwell, Peters, et al, 2018;Alleva, Martijn, et al, 2015).…”
Section: Methodological Quality Of Studiesmentioning
confidence: 99%
See 4 more Smart Citations
“…The EPHPP assessment (Thomas et al, 2004; see Table 3) revealed that the methodological quality of studies was mixed. Six studies were classified as weak, implying a high risk of bias (Albertson et al, 2015;Duarte et al, 2017;Jankowski et al, 2017;Mellor et al, 2017;Pinto-Gouveia et al, 2017;Pinto et al, 2003), six as moderate (Ahmadi et al, 2017;Annesi, 2005;Rodgers et al, 2018;Toole & Craighead, 2016;Wolfe & Patterson, 2017) and three (by the same author and using the same intervention) as strong, implying a low risk of bias (Alleva, Diedrichs, Halliwell, Martijn, et al, 2018;Alleva, Diedrichs, Halliwell, Peters, et al, 2018;Alleva, Martijn, et al, 2015).…”
Section: Methodological Quality Of Studiesmentioning
confidence: 99%
“…The studies took place in six countries: seven in the USA (Albertson et al, 2015;Annesi, 2005;Bush, Rossy, Mintz, & Schopp, 2014;Pinto, Clark, Maruyama, & Feder, 2003;Rodgers et al, 2018;Toole & Craighead, 2016;Wolfe & Patterson, 2017), three in the UK (Alleva, Diedrichs, Halliwell, Martijn, et al, 2018;Alleva, Diedrichs, Halliwell, Peters, et al, 2018;Jankowski et al, 2017), two in Portugal (Duarte, Pinto-Gouveia, & Stubbs, 2017;Pinto-Gouveia et al, 2017), and one study in Australia (Mellor, Connaughton, McCabe, & Tatangelo, 2017), Iran (Ahmadi, Abbaspoor, Behroozy, & Malehi, 2017), and the Netherlands (Alleva, Martijn, et al, 2015). There was significant variation in sample size between the studies, ranging from 20 to 274 participants (M = 105.7).…”
Section: Study Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations